2022
DOI: 10.3389/fncel.2022.855161
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Ameliorates Metabolic Changes Associated With Status Epilepticus in Immature Rats

Abstract: Status epilepticus (SE) is a common paediatric emergency with the highest incidence in the neonatal period and is a well-known epileptogenic insult. As previously established in various experimental and human studies, SE induces long-term alterations to brain metabolism, alterations that directly contribute to the development of epilepsy. To influence these changes, organic isothiocyanate compound sulforaphane (SFN) has been used in the present study for its known effect of enhancing antioxidative, cytoprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…The important question arises whether the protective effect of SFN could not be due to an anticonvulsant effect. However, the behavior pattern of seizures (latency, severity, frequency, duration) was not influenced in our study by SFN and the absence of the anticonvulsant effect of SFN has also been confirmed by EEG recordings (see [62] Supplementary Fig. 1).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The important question arises whether the protective effect of SFN could not be due to an anticonvulsant effect. However, the behavior pattern of seizures (latency, severity, frequency, duration) was not influenced in our study by SFN and the absence of the anticonvulsant effect of SFN has also been confirmed by EEG recordings (see [62] Supplementary Fig. 1).…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, similar findings were found by Luis-Garcia et al [58]. These authors, using the rodent experimental model of Huntington's disease induced by quinolinic acid, reported that sulforaphane attenuated effectively mitochondrial dysfunction by preventing the decrease of respiratory control ratio, Table 1 Effect of SNF associated with Li-pilocarpine-induced SE in immature rats (information taken from [62])…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In some cases, impaired energy metabolism may also contribute to or even cause epileptic seizures. 36,37 In rat chronic seizure models, the use of FDG and [ 14 C] DG also demonstrated decreases in glucose metabolism in brain areas presumed to be involved in seizure generation in several studies, 6,7,38,39 although others did not detect any significant differences, 40,41 which may be due to methodological detection limits. Importantly, several papers did not find correlations between the extent of hypometabolism and cell loss, indicating that, similar to data from people with epilepsy, hypometabolism is more widespread than the neuronal damage and occurs in remaining neurons and astrocytes.…”
Section: Interictal Hypometabolism In Epileptic Patients and Experime...mentioning
confidence: 99%